Comparative Analysis of Complication Rates between Open Circumcision and Plastibell Circumcision: A Systematic Review through Meta-analysis - Muhammad Salman; Javid Iqbal; Hamid Iqbal; Ali, Azmat (Indus Journal of Bioscience Research, 2024)
Background: Circumcision is a common surgical procedure, with open circumcision and Plastibell circumcision being popular methods. Objective: To compare complication rates between open circumcision and Plastibell circumcision through a systematic review and meta-analysis. Methods: A comprehensive database search identified 15 studies for inclusion. Data were extracted using standardized tools. Additionally, a prospective analysis of 119 children who underwent Plastibell circumcision was conducted, assessing surgical duration, device separation time, and complications. Follow-up occurred on days 15, 45, 90, and 120 post-surgery. Results: Children undergoing Plastibell circumcision were aged 2–12.5 years (mean 5.9 ± 2.9). Mean surgical duration was 3.7 ± 2.0 minutes, and device separation occurred in 6–26 days (mean 16 ± 4.2). Late complications occurred in 26.8% of cases, primarily minor issues such as preputial adhesions and mucosal edema, resolving with clinical treatment. Meta-analysis revealed Plastibell circumcision had significantly lower risks of bleeding (RR = 0.43, 95% CI = 0.24–0.76) and wound infection (RR = 0.35, 95% CI = 0.15–0.82) but higher risk of inadequate skin removal (RR = 2.35, 95% CI = 1.23–4.48). Conclusions: Plastibell circumcision has a lower risk of bleeding and infections compared to open circumcision, though risks of inadequate skin removal and phimosis are higher, particularly in older children. Parental satisfaction favored the open method for cosmetic outcomes but the Plastibell method for ease of care. Plastibell circumcision is efficient and safe for older children with proper anesthesia and follow-up.